2020
DOI: 10.1139/cjfas-2019-0136
|View full text |Cite
|
Sign up to set email alerts
|

Some like it slow: a bioenergetic evaluation of habitat quality for juvenile Chinook salmon in the Lemhi River, Idaho

Abstract: Management and conservation of freshwater habitat requires fine spatial resolution and watershed-scale and life-stage-specific methods due to complex linkages among land, climate, water uses, and aquatic organism necessities. In this study, we present a valley-scale microhabitat resolution, process-based bioenergetics approach that combines high-resolution topobathymetric LiDAR survey with two-dimensional hydrodynamic and bioenergetics modeling. We applied the model to investigate the role of lateral habitat, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 65 publications
(105 reference statements)
0
5
0
Order By: Relevance
“…Modeling approaches are becoming more widely used to evaluate the effects of different management scenarios for stream fishes. Studies to evaluate the effect of restoration efforts or predict future consequences of climate change are commonly based on the availability of suitable habitat for salmonid fishes (Jenkins and Keeley 2010;Urabe et al 2010;Carmichael et al 2020;Railsback et al 2021b). At the core of many such models, fish foraging behavior and estimates of food consumption are used to calculate energy intake and habitat suitability (Hughes and Dill 1990;Rosenfeld and Taylor 2009;Dodrill et al 2016;Hayes et al 2016;Railsback et al 2021a).…”
Section: Discussionmentioning
confidence: 99%
“…Modeling approaches are becoming more widely used to evaluate the effects of different management scenarios for stream fishes. Studies to evaluate the effect of restoration efforts or predict future consequences of climate change are commonly based on the availability of suitable habitat for salmonid fishes (Jenkins and Keeley 2010;Urabe et al 2010;Carmichael et al 2020;Railsback et al 2021b). At the core of many such models, fish foraging behavior and estimates of food consumption are used to calculate energy intake and habitat suitability (Hughes and Dill 1990;Rosenfeld and Taylor 2009;Dodrill et al 2016;Hayes et al 2016;Railsback et al 2021a).…”
Section: Discussionmentioning
confidence: 99%
“…As such, these models can be used to estimate growth from consumption or vice versa, while accounting for size‐ and temperature‐dependent effects on these physiological processes. Applications of these models range widely (see Deslauriers et al 2017 for review) but can include quantitative assessments of predation mortality (Lowery and Beauchamp 2015; Sorel et al 2016b) or consumption demand and carrying capacity (Sorel et al 2016a; Taylor et al 2020), estimating habitat quantity and growth potential (Weber et al 2014; Carmichael et al 2020), or evaluating possible distributional (Lawrence et al 2015) or trophic shifts due to climate change (Breeggemann et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Riparian plants, geomorphic features and valley extent influence the structure of fish populations. For example, Burnett (2001) observed that juvenile Chinook salmon ( O. tshawytscha ) prefer large, unconfined valleys due to the greater availability of slow‐water habitats compared to narrow, constrained valleys (Carmichael et al, 2020). Spawning by Chinook salmon has also been observed in high densities in large valleys where low gradient channels provide flow conditions that are suitable for nest building and riparian plants offer spawning adults and juvenile fish cover from predators (Buffington et al, 2004).…”
Section: Introductionmentioning
confidence: 99%